MORFOLOGI ALLUVIAL PLAIN DESA BUMIWANGI KECAMATAN CIPARAY - Aditya Al-Fikri Amanullah; Andiko Putra; Agung Aprilian Putra; Afrillia Tri Cahyani; Chriswanti Pangestu; Elfi Effendi; Fenando Hero Aliyandri; Geny Handani Putra; Syafrina Syafrina; Verdy Jainathul Khamsya; Risky Ramadhan (JURNAL BUANA, 2020)
South Bandung is one of the areas included in the Bandung Basin which is a mountainous region. Active and non-active volcanoes line up in this area, including Mt. Patuha, Mt. Puppet, and Mt. Windu Because of this South Bandung has abundant natural resource potential, including water resources, geothermal resources, and mining. Water sources lined up along the northern slopes of the mountains. Cisanti at the foot of Mount Wayang is the headwaters of the Citarum River which is the longest river in West Java.